Facilitating English Learners Competence in Listening through Flowerdew and Miller’s Listening Strategies - Diyan Anita Puspitasari; Slamet Setiawan; Ahmad Munir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to examine the use of listening strategies to facilitate the students’ listening competence and aims to examine the students’ perception about the roles of listening strategies. Using a qualitative research as the design of the research, the researcher collects the data through observation in listening classroom and interview to the university students. The result reveals that the lecturer used Flowerdew and Miller’ listening strategies, such as metacognitive strategies, cognitive strategies, and socioaffective strategies to facilitate the students in improving their listening competence, Moreover, the students perceive that the roles of listening strategies can help them to enhance their competence and help them become more skillful in listening. Keywords: Listening Strategies, Cognitive, Metacognitive, Socioaffective